Gastronomic Tourism: A bibliometric survey of National and International databases - Ribeiro-Martin, Clarissa de Souza (2017)
The aim of this study is to conduct a bibliometric survey on the construct of gastronomic tourism in the national and international periodical databases. Forty-five articles were identified in the Capes, Spell, Proquest and Ebsco databases, and analyzed. Different analyses were carried out, such as temporal evolution, identification of journals, calculation of the Bradford law, types of research carried out, Freeman’s centrality, author’s networks, Bonacich’s power measurement, comparative with Lotka’s law; networks of universities, works with the highest number of references, and main words mentioned in the objectives. It was verified, among other aspects, that the core of the subject is the periodicals: Casos and Rosa dos Ventos, as well as the journals Estudios y Perspectivas en Turismo, Tourism & Managemen, and TuryDes. The most referenced author is Michael Hall, but the work with most references is Erik Cohen. The researcher Emilio Morales-Fernández and the universities of Aveiro and Loyola Andalucía have the highest number of scientific partnerships.